Sinopse dos crustáceos decápodos brasileiros (Portunidae) - Coelho,Petrônio Alves (1992)
This paper presents a contribution to the study of the Crustacea, Decapoda of Brazil, including identification keys and informations on species range. Data related to the species of family Portunidae are published.